An Empirical Study of the Features of Coordination Functions in Hearing-Impaired Children of Primary School Age - L.N. Molchanova; A.V. Buzovkina (Клиническая и специальная психология)
The article examines the features of coordination functions (static, dynamic, spatial, object and symbolic coordination) in hearing-impaired children of primary school age from the perspective of N.A. Bernstein`s psychophysiological movement theory. According to this theory, there are five levels of the movement construction system: the level of static coordination (A), the level of dynamic coordination (B), the level of spatial coordination (C), the level of object coordination (D) and the level of symbolic coordination (E). 60 respondents took part in the study. 30 hearing-impaired primary schoolchildren (7–11 years old) with sensorineural hearing loss (13 girls and 17 boys) were included in the experimental group, and 30 primary schoolchildren (7–11 years old) without hearing impairment formed the control group (16 girls and 14 boys). The parameters of coordination functions were assessed using neuropsychological tests. A comparative analysis of the development of coordination functions in children from the experimental and control groups revealed a decrease in their dynamic characteristics such as pace and accuracy, which confirms the insufficiency of all these levels of movement organization in children of primary school age with sensorineural hearing loss, compared to children without hearing impairments.